Studi Keragaman Komunitas Gulma pada Areal Pertanaman Rambutan (Nephelium Lappaceum) Di Desa Hitu dan Desa Allang Kabupaten Maluku Tengah - Laura Tambung; Leonard Madubun; Vilma Laurien Tanasale; Nureny Goo (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2025)
The rambutan plant (Nephelium lappaceum) is a tropical fruit of the Sapindaceae family that is loved by the Indonesian people and is widely found in various regions, including Hitu Village and Allang Village, Central Maluku Regency. Rambutan production in this area tends to decrease every year, one of which is due to weed disturbances that inhibit plant growth. This study aims to identify the types of weeds that grow in the rambutan planting area in Hitu Village and Allang Village and determine the most dominant weed types in each location with different altitude conditions. The research was carried out using a vegetation survey method using sample plots measuring 1 m × 1 m under six rambutan trees in two different areas, so that a total of 12 weed samples were obtained. Data collected through field observation includes quantitative and qualitative data, both primary and secondary. The results of the study showed that there were 27 types of weeds in the entire rambutan planting area, namely 15 types in Hitu Village and 13 types in Allang Village. The dominant weed type in Hitu Village is Vigna luteola with an SDR value of 18.56%, while in Allang Village the dominant weed is Miconia crenata (Cahs) Michelang with an SDR value of 28.89%.